Jarimah Ta'zir dalam Penyebaran Konten Inses di Facebook Berdasarkan Maqashid Syariah - Andriyani Andriyani; Bela Meydarista; Nia Ramadhani; Radja Risky Ramadhan; Tiara Ardita; M. Reza Ramadhan; M. Ryan Hidayat (Journal of Sharia and Legal Science, 2026)
The phenomenon of the exposure of the Facebook group Incestuous Fantasi shows that social media can be a means of spreading pornographic content containing incest that involves sexual exploitation, including against children. This study aims to analyze the spread of incest content on Facebook from the perspective of Islamic criminal law, examine the basis for determining ta'zir jarimah sanctions against the perpetrators based on the fiqh of maqāṣid al-syarī'ah, and explain the relevance of the principles of saddu al-dzarī'ah and siyāsah syar'iyyah in overcoming these digital crimes. This study is a normative legal research with a conceptual approach. The results of the study indicate that the spread of incest content on Facebook is an act that falls into the category of ta'zir jarimah because there is no hadi provision that explicitly regulates the sanctions, but the act fulfills the elements of spreading fāḥisyah and ta'āwun 'alā al-itsm which are prohibited by sharia. The determination of ta'zir sanctions has a strong basis in the maqāṣid al-syarī'ah because it aims to protect religion (hifẓ al-dīn), soul (hifẓ al-nafs), reason (hifẓ al-'aql), descendants (hifẓ al-nasl), property (hifẓ al-māl), and honor (hifẓ al-'ird). In addition, the principle of saddu al-dzarī'ah provides legitimacy to preventive efforts in the form of blocking content and closing access to distribution, while siyāsah syar'iyyah authorizes the state to establish effective criminal policies in maintaining the public welfare in the digital space. This research contributes to the development of contemporary jinayah fiqh studies by offering a legal formulation that is responsive to the development of social media-based cybercrime.